The Planetary Nebula Luminosity Function in the Era of Precision Cosmology - Ciardullo, Robin (Frontiers in Astronomy and Space Sciences, 2022)
One of the great surprises of the late 1980s was the discovery that the [O III] λ5007 planetary nebula luminosity function (PNLF) could be used as a precision extragalactic standard candle. Despite the lack of any robust theory for the phenomenon, the technique passed a myriad of internal and external tests, and became an extremely reliable tool for obtaining distances to large galaxies within ~20 Mpc. But in more recent years, the use of the technique has declined, due in part to the changing landscape of cosmology. Here we review the history of the PNLF, the experiments that confirmed its utility, and the reasons why interest in the method faded at the turn of the millennium. We also describe how and why the PNLF is making a comeback, and present some of the method's recent results. Finally, we discuss how the PNLF must be analyzed in the era of precision cosmology, and detail the issues that must be overcome in order to address the current tension between local measures of the Hubble constant and values derived from the microwave background. If these issues can be understood, then the PNLF can provide a useful cross-check on distance measurements out to ~40 Mpc.